A novel variant of NPPC causes abnormal post-translational cleavage: A candidate gene for premature ovarian insufficiency. (March 2022) - Park, Jong-Yoon; Go, Minyeon; Lyu, Sang Woo; Yoon, Tae Ki; Kang, Kyung Min; Kim, Ji Won; Shim, Sung Han
Highlights: This study suggested the involvement of a novel genetic variant in the pathogenesis of premature ovarian insufficiency (POI). The 14 candidate variants in 13 genes were detected in nonconsanguineous family members with POI using whole exome sequencing. Genomic sequencing revealed novel variants in the NPPC gene. The cGMP activity of NPR2 -expressing cells was decreased by interaction with the mutant NPPC peptide secreted by the cells expressing NPPC 131A> G . A mutation of the NPPC gene might influence preantral follicle development and/or sustain meiotic arrest in oocytes. Abstract: Objective: Premature ovarian insufficiency (POI) is a clinical disease that is diagnosed by the loss of ovarian function before the age of 40. Despite recent progress in molecular diagnosis, the genetic etiology of POI is not well established. The aim of this study is to reveal pathogenic genetic variants involved in POI. Study design and main outcome measures: To reveal pathogenic genetic variants involved in POI, whole exome sequencing was performed in nonconsanguineous family members with POI. Constitutional variants were filtered against population databases and a missense mutation of natriuretic peptide C ( NPPC ) (c.131A> G, p.Q44R) was selected as a convincing candidate mutation among 14 heterozygous mutant alleles in 13 genes. Results: The wild-type NPPC and mutant NPPC ( NPPC 131A> G ) were expressed in HeLa cells, and cells expressing NPPC 131A> G secreted unique peptides. The ProP 1.0 Server, a neural network prediction tool, predicted the presence of a cleavage site at the substituted arginine residue (p.Q44R) of NPPC. The molecular weight of predicted cleaved peptides processed from mutant NPPC precursor corresponded to that of the actual mutant peptide. The cGMP synthetic activity of NPR2-expressing cells was significantly decreased by interaction with the mutant NPPC peptide compared with wild-type NPPC. Conclusions: The peptide generated by a rare mutation of NPPC might influence paracrine C-type natriuretic peptide (CNP)-mediated preantral follicle development and/or sustain meiotic arrest in oocytes. We therefore suggest that a mutation of the NPPC gene is involved in the pathogenesis of POI.